„Wir fahren jetzt nicht mit’m Mercedes vor, wenn man sich nachher eigentlich nur ‘n Polo leisten kann.“ Vorstellungen von Transfer in Theorie und Praxis der Beruflichen Bildung und ihre Implikationen - Daniel-Söltenfuß, Desiree

"Wir machen dann das, worauf wir Bock haben" - Eine empirische Analyse zur Bedeutung fachdidaktischer Überzeugungen für die unterrichtsbezogene Lehrerkooperation - Engemann, Mario

"Would You Give the Same Priority to the Bank and a Game? I Do Not!" Exploring Credential Management Strategies and Obstacles during Password Manager Setup - Amft, Sabrina; Höltervennhoff, Sandra; Huaman, Nicolas; Acar, Yasemin; Fahl, Sascha (Nineteenth Symposium on Usable Privacy and Security, SOUPS 2023, Anaheim, CA, USA, August 5-7, 2023)

„Zentral gelegenes Hotel im aufstrebenden Ferienort“. Hotelbeschreibungen zwischen Fakt und Fake. - Rezat, Sara (Praxis Deutsch)

#DIGITALENTS - Digital Talents Programm geht in die zweite Runde - Kundisch, Dennis

#SayTheirNames: Widerständige Medien der Erinnerung rechter Gewalt«, mit Sarah Horn - Degeling, Jasmin (feministische studien: Feministisches Erinnern)

$L^2$-spectrum, growth indicator function and critical exponent on locally symmetric spaces - Wolf, Lasse L.; Zhang, Hong-Wei (arXiv:2311.11770)
In this short note we observe, on locally symmetric spaces of higher rank, a connection between the growth indicator function introduced by Quint and the modified critical exponent of the Poincar\'e series equipped with the polyhedral distance. As a consequence, we provide a different characterization of the bottom of the $L^2$-spectrum of the Laplace-Beltrami operator in terms of the growth indicator function. Moreover, we explore the relationship between these three objects and the temperedness.

‚[M]uch too terrible for representation‘. Musik und Geräusch in Matthew Lewis’ Melodram The Captive (1803) - Ricke, Anna (Musik und das Unheimliche)

'He'd seen it in the words of Owen and Brooke': The Influence of Great War Poetry on Post-Millennium Soldier Poetry - Behler, Felix (Anglica: An International Journal of English Studies)

‘I Feel Well, Accepted and Competent in School’—Determinants of Self-Perceived Inclusion and Academic Self-Concept in Students with Diagnosed Behavioral, Emotional and Social Difficulties (BESD) - Zdoupas, Philippos; Laubenstein, Désirée (Social Sciences)

‘I had a patient who…’: Narratives of Vicarious Experience in GPs’ Discourse on Domestic Violence - Mildorf, Jarmila (Narrative Structure and Narrative Knowing in Medicine and Science)

‹Ich sehe was, was du nicht siehst…› Zu den Potenzialen von Sketchnoting im Kontext Inklusiver Medienbildung - Kückmann, Marie-Ann (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)
Wiederholt wird im Inklusionszusammenhang auf die Bedeutung von Medien verwiesen. Inklusion und Mediatisierung werden dabei als relevante, grundlegende gesellschaftliche Transformationen zunehmend zusammen gedacht. So wird im Kontext des Diskurses um inklusive Medienbildung immer wieder darauf hingewiesen, dass Medien eben Möglichkeiten zur Teilhabe und Interaktion bedingen und darüber entsprechend Kultur d. h. zugrundeliegende Inhalte, Werte usw. (mit) herstellen. Ausgehend von diesen Grundgedanken soll vorliegend neben Inklusion und Mediatisierung auch eine zunehmende Visualisierung als untrennbar miteinander verbundene Prozesse vor dem Hintergrund transformatorischer Bildung in den Blick genommen werden. So ist nicht zuletzt im Zuge digitaler Transformation festzustellen, dass visuelle Ausdrucksformen resp. neuere Kommunikationsmedien wie bspw. «Sketchnotes» vermehrt Eingang in unterschiedliche Lebensbereiche finden. So erfreuen sich etwa Ansätze wie «Graphic Recording» sowie «Visual Facilitation» sowohl im betrieblichen Kontext als auch im (Weiter-)Bildungsbereich zunehmender Beliebtheit. Dabei sind im Besonderen Fragen danach, was das Prinzip Sketchnoting als spezifische mediale Artikulation überhaupt ausmacht und inwiefern dieses hierauf aufbauend einen Beitrag zur inklusiven Medienbildung leisten kann, jedoch weitgehend ungeklärt. Der vorliegende Artikel widmet sich diesen und ähnlichen Fragestellungen aus theoretischer Perspektive, kennzeichnet Sketchnoting als grundlegenden dynamisch-dialektischen Prozess (also bspw. als Wechselspiel von Simultaneität und Sukzession, von Emotionsförderung und Versachlichung sowie von Abstrahierung und Konkretisierung), leitet aufbauend neuartige mediale Ausdrucks-, Interaktions- resp. Verständigungsmöglichkeiten ab und soll so auch einen Ausgangspunkt für weitere Diskussionen sowie für die empirische Forschung eröffnen.
Keywords: General Medicine

'Pappeln, die grüne Messer sind' und 'ratlose Brillenbären in Zoo'. Deformierte Naturverhältnisse bei Angela Krauß und Herta Müller - Morrien, Rita (Werke im Dialog. (Virtuelle) Begegnungen anlässlich von 40 Jahren Paderborner Gastdozentur für Schriftstellerinnen und Schriftsteller)

'Surprised, Shocked, Worried'}: User Reactions to Facebook Data Collection from Third Parties - Arias-Cabarcos, Patricia; Khalili, Saina; Strufe, Thorsten (Proceedings on Privacy Enhancing Technologies)
Data collection and aggregation by online services happens to an extent that is often beyond awareness and comprehension of its users. Transparency tools become crucial to inform people, though it is unclear how well they work. To investigate this matter, we conducted a user study focusing on Facebook, which has recently released the 'Off-Facebook Activity' transparency dashboard that informs about personal data collection from third parties. We exposed a group of n = 100 participants to the dashboard and surveyed their level of awareness and reactions to understand how transparency impacts users' privacy attitudes and intended behavior. Our participants were surprised about the massive amount of collected data, became significantly less comfortable with data collection, and more likely to take protective measures. Collaterally, we observed that current consent schemes are inadequate. Based on the survey findings, we make recommendations for more usable transparency and highlight the need to raise awareness about transparency tools and to provide easily actionable privacy controls.
Keywords: General Medicine

(K)ein Ende des „Alten Bundes“? Paulinische Schrifthermeneutik in 2 Kor 3 - Taschl-Erber, Andrea (Heilige Texte. Verständigungen zwischen Theologie und Kulturwissenschaft)

(K)ein Ende des "Alten Bundes"? Paulinische Schrifthermeneutik in 2 Kor 3, - Taschl-Erber, Andrea (Heilige Texte. Verständigungen zwischen Theologie und Kulturwissenschaft)

(Re-)inventing Biblical Traditions: The Representation of Pontius Pilate in Contemporary Historical Fiction - Behler, Felix (Narrative Ethics and Character in the Representation of the Past in Contemporary Fiction)

(Ver-)störendes Held*innentum. Figurationen und Repräsentationen von Soldatinnen und Soldaten in postheroischen Kriegszeiten - Böker, Ines (Limbus. Australisches Jahrbuch für germanistische Literatur und Kulturwissenschaft)

16 Fragen, 16 Antworten: In unserer Rubrik „Lehren im Leben” stellen wir Menschen vor, die Hochschullehre gestalten. Folge 6: Dr. Nerea Vöing - Vöing, Nerea (Lehren im Leben - Blog der Stiftung Innovation in der Hochschullehre)

2022 Global MNC Tax Complexity Survey - Harst, Simon; Schanz, Deborah; Siegel, Felix; Sureth-Sloane, Caren

3D-Druck – Eine Technologie als Schlüssel zur Steigerung der Teilhabe - Kruse, Anne; Müller, Laura; Ott, Manuel; Jung, Philipp; Koch, Rainer; Hügel, Joachim; Finke, Florian; Winter, Stephan; Gust, Thomas (Personennahe Dienstleistungen der Zukunft)

3D-structure of intermetallic interface layer in Al–steel clad material - Šlapáková, Michaela; Kihoulou, Barbora; Veselý, Jozef; Minárik, Peter; Fekete, Klaudia; Knapek, Michal; Králík, Rostislav; Grydin, Olexandr; Stolbchenko, Mykhailo; Schaper, Mirko (Vacuum)
This paper reveals the 3D character of the intermetallic layer at the aluminum–steel interface which pops up above the original sample surface during annealing. Popping out of the intermetallics was proven using atomic force microscopy. The phase expands out of the plane due to the exothermic formation of the Al5Fe2 phase and the feasibility of surface diffusion. Milling by a focused ion beam enabled the comparison of the chemical composition of the surface layer with the bulk interface, showing no difference. The growth direction is both towards aluminum and steel — the main diffusion flux is from aluminum towards steel, and the new intermetallic phase emerges at the steel side. The shortage of Al atoms causes a shift of the intermetallic as a whole towards aluminum.
Keywords: Al-steel clad; twin-roll casting; 3D characterization; atomic force microscopy; diffusion direction; surface growth

6.3.2 Medienpädagogische Professionalisierung in der beruflichen Weiterbildung. Eine Studie aus Perspektive der biografischen Medienforschung. Steckbrief zur Dissertation. - Dehmel, Lukas (Grundlagen der Erwachsenen- und Weiterbildungsforschung)

Deutsch für den Beruf [Sammelrezension] Sander, Isa-Lou; Efing, Christian (Hrsg.): Der Betrieb als Sprachlernort. Tübingen: Narr Francke Attempto, 2021 (Kommunizieren im Beruf, 4). -- ISBN 978-3-8233-8442-7. 264 Seiten, € 68,00. Tichy, Ellen; Tesch, Felicitas (Hrsg.): Deutsch in Fach und Beruf. Aktuelle Fragen und neue Ansätze der Fremdsprachenvermittlung. Berlin: Peter Lang, 2021 (Berufssprache Deutsch in Theorie und Praxis, 2). -- ISBN 978-3-631-79553-8. 194 Seiten, € 49,95. Niederhaus, Constanze: Deutsch für den Beruf. Eine Einführung. Berlin: Erich Schmidt, 2022 (Grundlagen Deutsch als Fremd- und Zweitsprache, 4). -- ISBN 978-3-503-20545-5. 265 Seiten, € 22,00. - Prikoszovits, Matthias (Informationen Deutsch als Fremdsprache)
Keywords: General Medicine

[Klopstocks] Liebe und Freundschaft - Elit, Stefan (Klopstock-Handbuch. Leben – Werk – Wirkung)

[Klopstocks] Sprachtheoretische Schriften - Elit, Stefan (Klopstock-Handbuch. Leben – Werk – Wirkung)

[zu:] Martin Kagel, David Z. Saltz (Ed.): Open Wounds: Holocaust Theater and the Le-gacy of George Tabori. - Eke, Norbert

A $C^k$-seeley-extension-theorem for Bastiani’s differential calculus - Hanusch, Maximilian (Canadian Journal of Mathematics)
Keywords: extension of differentiable maps

A 28-Gb/s 27.2mW NRZ Full-Rate Bang-Bang Clock and Data Recovery in 22 nm FD-SOI CMOS Technology - Iftekhar, Mohammed; Gowda, Harshan; Kneuper, Pascal; Sadiye, Babak; Müller, Wolfgang; Scheytt, Christoph (2023 IEEE BiCMOS and Compound Semiconductor Integrated Circuits and Technology Symposium (BCICTS))

A bi-objective hybrid vibration damping optimization model for synchronous flow shop scheduling problems - Tavana, Madjid; Hajipour, Vahid; Alaghebandha, Mohammad; Di Caprio, Debora (Machine Learning with Applications)
Keywords: General Medicine

A Bouquet of Encounters With Faux Flora Across Time – A Visual Essay. - Kraft, Kerstin

A calibration method for failure modeling in clinching process simulations - Böhnke, Max; Bielak, Christian Roman; Friedlein, Johannes; Bobbert, Mathias; Mergheim, Julia; Steinmann, Paul; Meschut, Gerson (Materials Research Proceedings)
Abstract. In the numerical simulation of mechanical joining technologies such as clinching, the material modeling of the joining parts is of major importance. This includes modeling the damage and failure behavior of the materials in accordance with varying occurring stress states. This paper presents a calibration method of three different fracture models. The calibration of the models is done by use of experimental data from a modified punch test, tensile test and bulge test in order to map the occurring stress states from clinching processes and to precisely model the resulting failure behavior. Experimental investigations were carried out for an aluminum alloy EN AW-6014 in temper T4 and compared with the simulative results generated in LS-DYNA. The comparison of force-displacement curves and failure initiation shows that the Hosford–Coulomb model predicts the failure behavior for the material used and the tests applied with the best accuracy.

A combinatorial data envelopment analysis with uncertain interval data with application to ICT evaluation - Santos-Arteaga, Francisco J.; Di Caprio, Debora; Tavana, Madjid (Technological Forecasting and Social Change)
Keywords: Management of Technology and Innovation; Applied Psychology; Business and International Management

A comparative performance analysis of intelligence-based algorithms for optimizing competitive facility location problems - Hajipour, Vahid; Niaki, Seyed Taghi Akhavan; Tavana, Madjid; Santos-Arteaga, Francisco J.; Hosseinzadeh, Sanaz (Machine Learning with Applications)
Keywords: General Medicine

A Comparison of Algorithms for the Generation of Layouts based on Reconfigurable Slots on FPGAs - Tadakamalla, Yashwanth

A Comparison of the Most Intense Periods (MIPs) During Competitive Matches and Training Over an 8-Week Period in a Male Elite Field Hockey Team - Büchel, Daniel; Döring, Michael; Baumeister, Jochen (Journal of Science in Sport and Exercise)
Abstract Purpose Wearables serve to quantify the on-court activity in intermittent sports such as field hockey (FH). Based on objective data, benchmarks can be determined to tailor training intensity and volume. Next to average and accumulated values, the most intense periods (MIPs) during competitive FH matches are of special interest, since these quantify the peak intensities players experience throughout the intermittent matches. The aim of this study was to retrospectively compare peak intensities between training and competition sessions in a male FH team competing in the first german division. Methods Throughout an 8-week in-season period, 372 individual activity datasets (144 datasets from competitive sessions) were recorded using the Polar Team Pro sensor (Kempele, Finland). MIPs were calculated applying a rolling window approach with predefined window length (1–5 min) and calculated for Total distance, High-Intensity-Running distance (> 16 km/h), Sprinting distance (> 20 km/h) and Acceleration load. Significant differences between training and competition MIPs were analysed through non-parametric statistical tests ( P < 0.05). Results Analyses revealed higher MIPs during competition for all considered outcomes ( P < 0.001). Effect size estimation revealed strongest effects for sprinting distance ( d = 1.89 to d = 1.22) and lowest effect sizes for acceleration load ( d = 0.92 to d = 0.49). Conclusion The present findings demonstrate that peak intensities during training do not reach those experienced during competitive sessions in a male FH team. Training routines such as manipulations of court-dimensions and team sizes might contribute to this discrepancy. Coaches should compare training and competition intensities to recalibrate training routines to optimize athletes’ preparation for competition.
Keywords: Nutrition and Dietetics; Rehabilitation; Orthopedics and Sports Medicine; Physical Therapy; Sports Therapy and Rehabilitation; Physiology

A computation of D(9) using FPGA Supercomputing - Van Hirtum, Lennart; De Causmaecker, Patrick; Goemaere, Jens; Kenter, Tobias; Riebler, Heinrich; Lass, Michael; Plessl, Christian (arXiv:2304.03039)
This preprint makes the claim of having computed the $9^{th}$ Dedekind Number. This was done by building an efficient FPGA Accelerator for the core operation of the process, and parallelizing it on the Noctua 2 Supercluster at Paderborn University. The resulting value is 286386577668298411128469151667598498812366. This value can be verified in two steps. We have made the data file containing the 490M results available, each of which can be verified separately on CPU, and the whole file sums to our proposed value.

A Credibility and Strategic Behavior Approach in Hesitant Multiple Criteria Decision-Making With Application to Sustainable Transportation - Santos-Arteaga, Francisco J.; Di Caprio, Debora; Tavana, Madjid; Tena, Emilio Cerda (IEEE Transactions on Fuzzy Systems)
Keywords: Applied Mathematics; Artificial Intelligence; Computational Theory and Mathematics; Control and Systems Engineering

A critical exponent for blow-up in a two-dimensional chemotaxis-consumption system - Ahn, Jaewook; Winkler, Michael (Calculus of Variations and Partial Differential Equations)
Keywords: Applied Mathematics; Analysis

A crystalline aluminium–carbon-based ambiphile capable of activation and catalytic transfer of ammonia in non-aqueous media - Krämer, Felix; Paradies, Jan; Fernández, Israel; Breher, Frank (Nature Chemistry)
Keywords: General Chemical Engineering; General Chemistry

A Data Map for Product Creation: Tasks, Data Flows, and IT-Systems from the Initial Idea to the Start of Production - Ködding, Patrick; Tissen, Denis; Koldewey, Christian (Proceedings of the 56th CIRP Conference on Manufacturing Systems, CIRP CMS ‘23)

A finite strain gradient theory for viscoplasticity by means of micromorphic regularization - Hamdoun, Ayoub; Mahnken, Rolf (PAMM)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

A finite strain gradient theory for viscoplasticity by means of micromorphic regularization - Hamdoun, Ayoub; Mahnken, Rolf (PAMM)
Abstract Stretching of polycarbonate films leads to the formation of shear bands in the necking zone [1]. Standard viscoplastic material models render mesh size dependent results, which requires a mathematical regularization. To this end, we present a finite strain gradient theory for a viscoplastic, isotropic material model where we extend the model presented in [2] to a micromorphic model by introducing a new micromorphic variable as an additional degree of freedom with its first gradient [3, 4]. The variable here has the meaning of a micro plastic strain, and is coupled with the macro plastic by a micro penalty term, forcing the macro‐plastic strain to be close to the micro‐plastic strain for the targeted shear band regularization effect. We have implemented the model equations as a three dimensional initial boundary value problem in an in house FE‐tool, to simulate different geometries with different thickness and to compare it the experimental tests. The analysis is performed for a uniaxial tensile geometry as well as for a biaxial tensile geometry. The numerical examples show the ability of the model to regularize the shear bands and solve the problem of localization.

A Force Field for Bio-Polymers in Ionic Liquids (BILFF) – Part 2: Cellulose in [EMIm][OAc] / Water Mixtures - Roos, E.; Sebastiani, D.; Brehm, Martin (Phys. Chem. Chem. Phys.)

A Framework For The Domain-Driven Utilization Of Manufacturing Sensor Data In Process Mining: An Action Design Approach - Brock, Jonathan; Rempe, Niclas; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (5th Conference on Production Systems and Logistics)

A fuzzy multi-objective optimization model for sustainable location planning using volumetric fuzzy sets - Tavana, Madjid; Arman, Hosein; Hadi-Vencheh, Abdollah; Mansoori, Sadegh (Annals of Operations Research)

A fuzzy preference programming and weighted influence non-linear gauge system for mission architecture assessment at NASA - Tavana, Madjid; Heidary, Mohammad Saeed; Mina, Hassan (Applied Soft Computing)
Keywords: Software

A Game-Theoretic Framework for Analyzing the Impact of Social Responsibility and Supply Chain Profitability - Mahdiraji, Hannan Amoozad; Tavana, Madjid; Rezayar, Ali (Cybernetics and Systems)
Keywords: Artificial Intelligence; Information Systems; Software

A general Best-Worst method considering interdependency with application to innovation and technology assessment at NASA - Tavana, Madjid; Mina, Hassan; Santos-Arteaga, Francisco J. (Journal of Business Research)
Keywords: Marketing

A Generic Construction of an Anonymous Reputation System and Instantiations from Lattices - Blömer, Johannes; Bobolz, Jan; Porzenheim, Laurens Alexander

A Hardware/Software Co-designed ORB-SLAM2 Algorithm for FPGA - Thiele, Simon

A hesitant fuzzy group decision-making framework with data credibility and strategic evaluations - Tavana, Madjid; Keikha, Abazar; Santos-Arteaga, Francisco J. (Soft Computing)

A hybrid multi-attribute decision-making and data envelopment analysis model with heterogeneous attributes: The case of sustainable development goals - Soltanifar, Mehdi; Tavana, Madjid; Santos-Arteaga, Francisco J.; Sharafi, Hamid (Environmental Science & Policy)
Keywords: Management; Monitoring; Policy and Law; Geography; Planning and Development

A life cycle assessment of joining processes in the automotive industry, illustrated by the example of an EV battery case - Brunner-Schwer, Christian; Biegler, Max; Rethmeier, Michael; Schmolke, Tobias; Meschut, Gerson; Spohr, Sebastian; Eckstein, Lutz

A Lower Bound on the Critical Momentum of an Impurity in a Bose-Einstein Condensate - Hinrichs, Benjamin; Lampart, Jonas (arXiv:2311.05361)
In the Bogoliubov-Fr\"ohlich model, we prove that an impurity immersed in a Bose-Einstein condensate forms a stable quasi-particle when the total momentum is less than its mass times the speed of sound. The system thus exhibits superfluid behavior, as this quasi-particle does not experience friction. We do not assume any infrared or ultraviolet regularization of the model, which contains massless excitations and point-like interactions.

A Marxist-Humanist Perspective on Stuart Hall's Communication Theory - Fuchs, Christian (Theory and Society)

A Memetic NSGA-II for the Multi-Objective Flexible Job Shop Scheduling Problem with Real-time Energy Tariffs - Burmeister, Sascha Christian; Guericke, Daniela; Schryen, Guido (Flexible Services and Manufacturing Journal)

A Methodical Approach to Hybrid Modelling for Contextual Anomaly Detection on Time-Series Data - Lenz, Cederic; Henke, Christian; Trächtler, Ansgar (2023 IEEE 21st International Conference on Industrial Informatics (INDIN))

A micropolar model accounting for asymmetric behavior of cold‐box sand in relation to tensile and compression tests - Börger, Alexander; Mahnken, Rolf (PAMM)
Abstract Cold‐box sand (CBS) belongs to the granular materials and consists of sand and a binder. The behavior of CBS is simulated with a micropolar model, whereby the additional degree of freedom of the model describes the rotation of the sand grains. The model is used to generate a shear band under pressure for three different meshes, where the force‐displacement curves of the three meshes converge so that no mesh dependence occurs. Another requirement of the model is the consideration of asymmetric behavior for compression and tension. Due to the additional degree of freedom the implicit implementation of the micropolar continuum is very time‐consuming. Therefore, an explicit implementation is considered as an alternative possibility. This paper compares the advantages and disadvantages of both methods and the results for both calculations.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

A mixed-methods study of the quality of parental support during adolescents' information-related Internet use as a co-construction process - Kurock, Ricarda; Teichert, Jeannine; Meister, Dorothee M.; Gerhardts, Lara; Buhl, Heike M.; Bonanati, Sabrina (Journal of Adolescence)

A model of cycles and bubbles under heterogeneous beliefs in financial markets - Burs, Carina (Cogent Economics & Finance)
I study the effect of heterogeneous beliefs about asset prices on the long-term behavior of financial markets. Starting from the ideas of Abreu and Brunnermeier (Citation2003), a two-dimensional system of differential equations is developed. The first dynamic variable is the asset price growth rate. The second dynamic variable is the number of investors who believe that asset prices are abnormally high. In a phase plane analysis, I find both stable and unstable equilibria, depending on the spread of information and the response to other agents’ beliefs. If individuals try to increase their returns while perceiving more overpricing, these equilibria can be spirals or even approach limit cycles. Although I intend to study general price patterns, abnormally high asset prices can be caused by financial bubbles. In this model, bubbles can emerge and deflate both in cycles or directly, or they can grow until they burst. Further, I analyze market behavior after a central bank increases the interest rate. This can lead to new stable equilibria, but the emergence and bursting of bubbles cannot be prevented.
Keywords: asset pricing; subjective information; stability conditions; monetary policy; risk aversion

A multi-mode super-fano mechanism for enhanced third harmonic generation in silicon metasurfaces - Hähnel, David; Golla, Christian; Albert, Maximilian; Zentgraf, Thomas; Myroshnychenko, Viktor; Förstner, Jens; Meier, Cedrik (Light: Science & Applications)
We present strong enhancement of third harmonic generation in an amorphous silicon metasurface consisting of elliptical nano resonators. We show that this enhancement originates from a new type of multi-mode Fano mechanism. These ‘Super-Fano’ resonances are investigated numerically in great detail using full-wave simulations. The theoretically predicted behavior of the metasurface is experimentally verified by linear and nonlinear transmission spectroscopy. Moreover, quantitative nonlinear measurements are performed, in which an absolute conversion efficiency as high as ηmax ≈ 2.8 × 10−7 a peak power intensity of 1.2 GW cm−2 is found. Compared to an unpatterned silicon film of the same thickness amplification factors of up to ~900 are demonstrated. Our results pave the way to exploiting a strong Fano-type multi-mode coupling in metasurfaces for high THG in potential applications.
Keywords: tet_topic_meta

A multiobjective continuation method to compute the regularization path of deep neural networks - Amakor, Augustina Chidinma; Sonntag, Konstantin; Peitz, Sebastian (arXiv)
Sparsity is a highly desired feature in deep neural networks (DNNs) since it ensures numerical efficiency, improves the interpretability of models (due to the smaller number of relevant features), and robustness. In machine learning approaches based on linear models, it is well known that there exists a connecting path between the sparsest solution in terms of the $\ell^1$ norm,i.e., zero weights and the non-regularized solution, which is called the regularization path. Very recently, there was a first attempt to extend the concept of regularization paths to DNNs by means of treating the empirical loss and sparsity ($\ell^1$ norm) as two conflicting criteria and solving the resulting multiobjective optimization problem. However, due to the non-smoothness of the $\ell^1$ norm and the high number of parameters, this approach is not very efficient from a computational perspective. To overcome this limitation, we present an algorithm that allows for the approximation of the entire Pareto front for the above-mentioned objectives in a very efficient manner. We present numerical examples using both deterministic and stochastic gradients. We furthermore demonstrate that knowledge of the regularization path allows for a well-generalizing network parametrization.

A Narrowband Four-Quadrant Electro-Optical Mixer for Microwave Photonics - Kruse, Stephan; Greitens, Jan C.; Schwabe, Tobias; Kneuper, Pascal; Kurz, Heiko G.; Scheytt, J. Christoph (IEEE Microwave and Wireless Technology Letters)

A new algorithmic imaginary - Schulz, Christian (Media, Culture & Society)
The algorithmic imaginary as a theoretical concept has received increasing attention in recent years as it aims at users’ appropriation of algorithmic processes operating in opacity. But the concept originally only starts from the users’ point of view, while the processes on the platforms’ side are largely left out. In contrast, this paper argues that what is true for users is also valid for algorithmic processes and the designers behind. On the one hand, the algorithm imagines users’ future behavior via machine learning, which is supposed to predict all their future actions. On the other hand, the designers anticipate different actions that could potentially performed by users with every new implementation of features such as social media feeds. In order to bring into view this permanently reciprocal interplay coupled to the imaginary, in which not only the users are involved, I will argue for a more comprehensive and theoretically precise algorithmic imaginary referring to the theory of Cornelius Castoriadis. In such a perspective, an important contribution can be formulated for a theory of social media platforms that goes beyond praxeocentrism or structural determinism.
Keywords: Sociology and Political Science; Communication

A NEW APPROACH FOR THE LOCAL DETERMINATION OF ENERGY INPUT IN CO-ROTATING TWIN SCREW EXTRUDERS BASED ON SCREW TORSION - Schöppner, Volker; Austermeier, Laura; Nordieker, A.

A new approach to model the fluid dynamics in sandwich packings - Franke, Patrick; Shabanilemraski, Iman; Schubert, Markus; Hampel, Uwe; Kenig, Eugeny Y. (Chemical Product and Process Modeling)
Abstract Sandwich packings represent new separation column internals, with a potential to intensify mass transfer. They comprise two conventional structured packings with different specific geometrical surface areas. In this work, the complex fluid dynamics in sandwich packings is modeled using a novel approach based on a one-dimensional, steady momentum balance of the liquid and gas phases. The interactions between the three present phases (gas, liquid, and solid) are considered by closures incorporated into the momentum balance. The formulation of these closures is derived from two fluid-dynamic analogies for the film and froth flow patterns. The adjustable parameters in the closures are regressed for the film flow using dry pressure drop measurements and liquid hold-up data in trickle flow conditions. For the froth flow, the tuning parameters are fitted to overall pressure drop measurements and local liquid hold-up data acquired from ultra-fast X-ray tomography (UFXCT). The model predicts liquid hold-up and pressure drop data with an average relative deviation of 16.4 % and 19 %, respectively. Compared to previous fluid dynamic models for sandwich packings, the number of adjustable parameters could be reduced while maintaining comparable accuracy.
Keywords: Modeling and Simulation; General Chemical Engineering

A new dual matrix burner for one-dimensional investigation of aerosol flames - Apazeller, Sascha; Gonchikzhapov, Munko; Nanjaiah, Monika; Kasper, Tina; Wlokas, Irenäus; Wiggers, Hartmut; Schulz, Christof (Proceedings of the Combustion Institute)
In spray-flame synthesis of nanoparticles, a precise understanding of the reaction processes is necessary to find optimal process parameters for the formation of the desired products. Coupling the chemistries of flame, solvent, and gas-phase species initially formed from the particle precursor in combination with the complex flow geometry of the spray flame means a special challenge for the modeling of the reaction processes. A new burner has been developed that is capable to observe the reaction of precursor solutions frequently used in spray-flame synthesis. The burner provides an almost flat, laminar, and steady flame with homogeneous addition of a fine aerosol and thus enables detailed investigation and modeling of the coupled reactions inde-pendent of spray formation and turbulent mixing. With its two separate supply channel matrices, the burner also enables the use of reactants that would otherwise react with each other already before reaching the flame. These features enable the investigation of a wide range of flame-based synthesis methods for nanoparticles and, due to the flat-flame geometry, kinetics models for these processes can be developed and validated. This work describes the matrix burner development and its gas flow optimization by simulation. Droplet-size dis-tributions generated by ultrasonic nebulization and their interaction with the burner structure are investigated by phase-Doppler anemometry. As an example for nanoparticle-for ming flames from solutions, iron-oxide nanoparticle-generating flames using iron(III) nitrate nonahydrate dissolved in 1-butanol were investigated. This effort includes measurements of two-dimensional maps of the flame temperature by a thermocouple and height-dependent concentration profiles of the main species by time-of-flight mass spectrometry. Exper-imental data are compared with 1D simulations using a reduced reaction mechanism. The results show that the new burner is well suited for the development of reaction models for precursors supplied in the liquid phase usually applied in spray-flame synthesis configurations.& COPY; 2022 The Combustion Institute. Published by Elsevier Inc. All rights reserved.
Keywords: Physical and Theoretical Chemistry; Mechanical Engineering; General Chemical Engineering

A new dual matrix burner for one-dimensional investigation of aerosol flames - Apazeller, Sascha; Gonchikzhapov, Munko; Nanjaiah, Monika; Kasper, Tina; Wlokas, Irenäus; Wiggers, Hartmut; Schulz, Christof (Proceedings of the Combustion Institute)
Keywords: Physical and Theoretical Chemistry; Mechanical Engineering; General Chemical Engineering

A new strategic approach for R&D project portfolio selection using efficiency-uncertainty maps - Namazi, Mehdi; Tavana, Madjid; Mohammadi, Emran; Bonyadi Naeini, Ali (Benchmarking: An International Journal)
Purpose New business practices and the globalization of markets force firms to take innovation as the fundamental pillar of their competitive strategy. Research and Development (R&D) plays a vital role in innovation. As technology advances and product life cycles become shorter, firms rely on R&D as a strategy to invigorate innovation. R&D project portfolio selection is a complex and challenging task. Despite the management's efforts to implement the best project portfolio selection practices, many projects continue to fail or miss their target. The problem is that selecting R&D projects requires a deep understanding of strategic vision and technical capabilities. However, many decision-makers lack technological insight or strategic vision. This article aims to provide a method to capitalize on the expertise of R&D professionals to assist managers in making informed and effective decisions. It also provides a framework for aligning the portfolio of R&D projects with the organizational vision and mission. Design/methodology/approach This article proposes a new strategic approach for R&D project portfolio selection using efficiency-uncertainty maps. Findings The proposed strategy plane helps decision-makers align R&D project portfolios with their strategies to combine a strategic view and numerical analysis in this research. The proposed strategy plane consists of four areas: Exploitation Zone, Challenge Zone, Desperation Zone and Discretion Zone. Mapping the project into this strategic plane would help decision-makers align their project portfolio according to the corporate perspectives. Originality/value The new approach combines the efficiency and uncertainty dimensions in portfolio selection into an integrated framework that: (i) provides a complete representation of the stochastic decision-making processes, (ii) models the endogenous uncertainty inherent in the project selection process and (iii) proposes a computationally practical and visually unique solution procedure for classifying desirable and undesirable R&D projects.
Keywords: Business and International Management; Strategy and Management

A Non-Linear Mean-Field Debonding Model at Large Strains for the Analysis of Fibre Kinking in Ud Composites - Cheng, Chun; Song, Chunlei; Mahnken, Rolf; Yuan, Zhipeng; Yu, Liang; Ju, Xiaozhe

A novel indicator for sustainability in production planning using Center of Gravity-based assessment of Pareto fronts - Hilbert, Markus; Dellnitz, Andreas; Kleine, Andreas; Tavana, Madjid (Computers & Industrial Engineering)
Keywords: General Engineering; General Computer Science

A novel median-based optimization model for eco-efficiency assessment in data envelopment analysis - Dellnitz, Andreas; Tavana, Madjid; Banker, Rajiv (Annals of Operations Research)
Keywords: Management Science and Operations Research; General Decision Sciences

A pairing formula for resonant states on finite regular graphs - Hilgert, Joachim; Arends, C.; Frahm, J.

A parametrisation method for high-order phase reduction in coupled oscillator networks - von der Gracht, Sören; Nijholt, Eddie; Rink, Bob (arXiv:2306.03320)
We present a novel method for high-order phase reduction in networks of weakly coupled oscillators and, more generally, perturbations of reducible normally hyperbolic (quasi-)periodic tori. Our method works by computing an asymptotic expansion for an embedding of the perturbed invariant torus, as well as for the reduced phase dynamics in local coordinates. Both can be determined to arbitrary degrees of accuracy, and we show that the phase dynamics may directly be obtained in normal form. We apply the method to predict remote synchronisation in a chain of coupled Stuart-Landau oscillators.

A PRACTICAL HANDBOOK ON EFFECTIVE DEVELOPMENT AND IMPLEMENTATION OF STEAM TEACHING AT SCHOOL

A process mining maturity model: Enabling organizations to assess and improve their process mining activities - Brock, Jonathan; Löhr, Bernd; Brennig, Katharina; Seger, Thilo; Bartelheimer, Christian; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (ECIS 2023 Proceedings at AIS Electronic Library (AISeL).)

A Process Mining Maturity Model: Enabling Organizations to Assess and Improve their Process Mining Activities - Brock, Jonathan; Löhr, Bernd; Brennig, Katharina; Seger, Thilo; Bartelheimer, Christian; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (European Conference on Information Systems)
Organizations employ process mining to discover, check, or enhance process models based on data from information systems to improve business processes. Even though process mining is increasingly relevant in academia and organizations, achieving process mining excellence and generating business value through its application is elusive. Maturity models can help to manage interdisciplinary teams in their efforts to plan, implement, and manage process mining in organizations. However, while numerous maturity models on business process management (BPM) are available, recent calls for process mining maturity models indicate a gap in the current knowledge base. We systematically design and develop a comprehensive process mining maturity model that consists of five factors comprising 23 elements, which organizations need to develop to apply process mining sustainably and successfully. We contribute to the knowledge base by the exaptation of existing BPM maturity models, and validate our model through its application to a real-world scenario.

A process-model for tailoring prototyping of cyber-physical systems - Tissen, Denis; Koldewey, Christian; Dumitrescu, Roman

A Pulsed Lidar System With Ultimate Quantum Range Accuracy - Kruse, Stephan; Serino, Laura; Folge, Patrick Fabian; Echeverria Oviedo, Dana; Bhattacharjee, Abhinandan; Stefszky, Michael; Scheytt, J. Christoph; Brecht, Benjamin; Silberhorn, Christine (IEEE Photonics Technology Letters)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

A quantitative strong parabolic maximum principle and application to a taxis-type migration–consumption model involving signal-dependent degenerate diffusion - Winkler, Michael (Annales de l'Institut Henri Poincaré C, Analyse non linéaire)
Keywords: Mathematical Physics; Analysis; Applied Mathematics

A Reference Process Model for Scenario-based Foresight - Ködding, Patrick; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the XXXII ISPIM Innovation Conference)

A Regret Policy for the Dynamic Vehicle Routing Problem with Time Windows - Dieter, Peter (Lecture Notes in Computer Science)

A Riemann-Roch formula for singular reductions by circle actions - Delarue, Benjamin; Ioos, Louis; Ramacher, Pablo (arXiv:2302.09894)
We compute a Riemann-Roch formula for the invariant Riemann-Roch number of a quantizable Hamiltonian $S^1$-manifold $(M,ω,\mathcal{J})$ in terms of the geometry of its symplectic quotient, allowing $0$ to be a singular value of the moment map $\mathcal{J}:M→\mathbb{R}$. The formula involves a new explicit local invariant of the singularities. Our approach relies on a complete singular stationary phase expansion of the associated Witten integral.

A Social Network Approach for Investigating Social Influences on Effective Use: Demonstration in Virtual Reality Collaboration - Tölle, Laura; Slawinski, Elena; Fromm, Jennifer; Mirbabaie, Milad

A study on the effects of normalized TSP features for automated algorithm selection - Heins, Jonathan; Bossek, Jakob; Pohl, Janina; Seiler, Moritz; Trautmann, Heike; Kerschke, Pascal (Theoretical Computer Science)
Classic automated algorithm selection (AS) for (combinatorial) optimization problems heavily relies on so-called instance features, i.e., numerical characteristics of the problem at hand ideally extracted with computationally low-demanding routines. For the traveling salesperson problem (TSP) a plethora of features have been suggested. Most of these features are, if at all, only normalized imprecisely raising the issue of feature values being strongly affected by the instance size. Such artifacts may have detrimental effects on algorithm selection models. We propose a normalization for two feature groups which stood out in multiple AS studies on the TSP: (a) features based on a minimum spanning tree (MST) and (b) nearest neighbor relationships of the input instance. To this end we theoretically derive minimum and maximum values for properties of MSTs and k-nearest neighbor graphs (NNG) of Euclidean graphs. We analyze the differences in feature space between normalized versions of these features and their unnormalized counterparts. Our empirical investigations on various TSP benchmark sets point out that the feature scaling succeeds in eliminating the effect of the instance size. A proof-of-concept AS-study shows promising results: models trained with normalized features tend to outperform those trained with the respective vanilla features.
Keywords: Feature normalization; Algorithm selection; Traveling salesperson problem

A Sub-Threshold Microwave RFID Tag Chip, Compatible With RFID MIMO Reader Technology - Haddadian, Sanaz; Scheytt, J. Christoph; von Bögel, Gerd; Grenter, Thorben (IEEE Journal of Radio Frequency Identification)
We present a fully integrated radio frequency identifications transponder chip operating at 5.8 GHz, which is compatible with the class-1 generation-2 of the Electronic Product Code protocol (EPC-C1 G2). The tag chip including the analog front-end and the digital baseband processor, are designed in the sub-threshold regime (0.5 V) with a total supply current of less than 50 μA. As a power scavenging unit, a single-stage differential-drive rectifier structure is designed and fabricated with standard threshold voltage (SVT) MOS elements in a commercial 65-nm CMOS process, to provide 0.8 V of rectified voltage. Measurements performed on the fabricated single-stage structure show a maximum power conversion efficiency of 69.6% for a 22 kΩ load and a sensitivity of -12.5 dBm, which corresponds to more than 1 m of reading range. The power conversion efficiency at this range is about 64%.

A sustainable circular supply chain network design model for electric vehicle battery production using internet of things and big data - Tavana, Madjid; Sohrabi, Mahsa; Rezaei, Homa; Sorooshian, Shahryar; Mina, Hassan (Expert Systems)

A systematic literature review on the Digital Twin of the factory in the context of the product and factory lifecycle - Cieply, Jonas; Disselkamp, Jan-Philipp; Dyck, Florian; Alturk, Waddah; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

A Teacher-Student Approach for Extracting Informative Speaker Embeddings From Speech Mixtures - Cord-Landwehr, Tobias; Boeddeker, Christoph; Zorilă, Cătălin; Doddipatla, Rama; Haeb-Umbach, Reinhold (INTERSPEECH 2023)

A Technology Foresight Maturity Model - Ellermann, Kai; Asmar, Laban; Dumitrescu, Roman (ISPIM Conference Proceedings)

A thermodynamic framework for the phase‐field approach considering carbide precipitation during phase transformations - Westermann, Hendrik; Mahnken, Rolf (PAMM)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

A Topic Model for the Data Web - Röder, Michael; Kuchelev, Denis; Ngonga Ngomo, Axel-Cyrille (Knowledge Graphs and Semantic Web)
Keywords: sail dice roeder kuchelev ngonga

A Unifying Approach to Efficient (Near-)Gathering of Disoriented Robots with Limited Visibility - Castenow, Jannik; Harbig, Jonas; Jung, Daniel; Kling, Peter; Knollmann, Till; Meyer auf der Heide, Friedhelm (Proceedings of the 26th International Conference on Principles of Distributed Systems (OPODIS))

A Validation Study for the German Versions of the Feeling Scale and the Felt Arousal Scale for a Progressive Muscle Relaxation Exercise - Thorenz, Kristin; Berwinkel, Andre; Weigelt, Matthias (Behavioral Sciences)
The aim of the present study is to prove the construct validity of the German versions of the Feeling Scale (FS) and the Felt Arousal Scale (FAS) for a progressive muscle relaxation (PMR) exercise. A total of 228 sport science students conducted the PMR exercise for 45 min and completed the FS, the FAS, and the Self-Assessment Manikin (SAM) in a pre-test–post-test design. A significant decrease in arousal (t(227) = 8.296, p < 0.001) and a significant increase in pleasure (t(227) = 4.748, p < 0.001) were observed. For convergent validity, the correlations between the FS and the subscale SAM-P for the valence dimension (r = 0.67, p < 0.001) and between the FAS and the subscale SAM-A for the arousal dimension (r = 0.31, p < 0.001) were significant. For discriminant validity, the correlations between different constructs (FS and SAM-A, FAS and SAM-P) were not significant, whereas the discriminant analysis between the FS and the FAS revealed a negative significant correlation (r = −0.15, p < 0.001). Together, the pattern of results confirms the use of the German versions of the FS and the FAS to measure the affective response for a PMR exercise.
Keywords: Behavioral Neuroscience; General Psychology; Genetics; Development; Ecology; Evolution; Behavior and Systematics

A Validation Study of the German Versions of the Feeling Scale and the Felt Arousal Scale for a Passive Relaxation Technique (Autogenic Training) - Thorenz, Kristin; Berwinkel, Andre; Weigelt, Matthias (Psychology)
Keywords: General Earth and Planetary Sciences; General Environmental Science

A Viewpoint on Human Factors in Software Supply Chain Security: A Research Agenda - Fourné, Marcel; Wermke, Dominik; Fahl, Sascha; Acar, Yasemin (IEEE Secur. Priv.)

A Viewpoint on Human Factors in Software Supply Chain Security: A Research Agenda - Fourné, Marcel; Wermke, Dominik; Fahl, Sascha; Acar, Yasemin (IEEE Security & Privacy)

A World Full of Privacy and Security (Mis)conceptions? Findings of a Representative Survey in 12 Countries - Herbert, Franziska; Becker, Steffen; Schaewitz, Leonie; Hielscher, Jonas; Kowalewski, Marvin; Sasse, M. Angela; Acar, Yasemin; Dürmuth, Markus (Proceedings of the 2023 CHI Conference on Human Factors in Computing Systems, CHI 2023, Hamburg, Germany, April 23-28, 2023)

ABHÄNGEN - Ein- und Ausgrenzen, Kanonisieren, Kollaborieren in Pop, Kunst und Medien - Jacke, Christoph (Impulse. Texte und Bilder zur Kunstvermittlung)

ABHÄNGEN - Ein- und Ausgrenzen, Kanonisieren, Kollaborieren in Pop, Kunst und Medien. - Jacke, Christoph (Impulse. Texte und Bilder zur Kunstvermittlung.)

Abhängenwerden. Fühlen und Denken - Jacke, Christoph (Impulse. Texte und Bilder zur Kunstvermittlung)

Abhängenwerden. Fühlen und Denken. - Jacke, Christoph (Impulse. Texte und Bilder zur Kunstvermittlung.)

ABIS 2023 – 27th International Workshop on Personalization and Recommendation - Neumayr, Thomas; Yigitbas, Enes; Augstein, Mirjam; Herder, Eelco (Proceedings of the Mensch & Computer (2023))

Abkommen der EU - Krimphove, Dieter (Manz Online)

Ableitung flacher Probengeometrien zur Abbildung mehraxialer Spannungszustände in Clinchverbindungen unter zyklischer Beanspruchung - Ewenz, Lars; Kuczyk, Martin; Schöne, S.; Zimmermann, Martina (Tagung Werkstoffprüfung 2022)

Abschlussbericht zum Forschungsprojekt ‚Gelingensbedingungen und Transfer von erfolgreichen Digitalisierungsprozessen an Schulen in Nordrhein-Westfalen (GuTe DigiSchulen NRW) - Gerick, J.; Eickelmann, Birgit; Panten, B.; Rothärmel, A.; Rau, M.; Gottschalk, T.

Absence of collapse into persistent Dirac-type singularities in a Keller-Segel-Navier-Stokes system involving local sensing - Winkler, Michael (Advances in Differential Equations)
Keywords: Applied Mathematics; Analysis

Absence of principal eigenvalues for higher rank locally symmetric spaces - Weich, Tobias; Wolf, Lasse Lennart (Communications in Mathematical Physics)
Given a geometrically finite hyperbolic surface of infinite volume it is a classical result of Patterson that the positive Laplace-Beltrami operator has no $L^2$-eigenvalues $≥ 1/4$. In this article we prove a generalization of this result for the joint $L^2$-eigenvalues of the algebra of commuting differential operators on Riemannian locally symmetric spaces $Γ\backslash G/K$ of higher rank. We derive dynamical assumptions on the $Γ$-action on the geodesic and the Satake compactifications which imply the absence of the corresponding principal eigenvalues. A large class of examples fulfilling these assumptions are the non-compact quotients by Anosov subgroups.

Abstract Reflection in Contemporary Fiction (Anglia)

Academic self-concepts of pre-service technology teachers for vocational education in Germany according to the TPACK- Model - Vernholz, Mats (Living and Leading in the Next Era: Connecting Teaching, Research, Citizenship and Equity)

acatech Maturity Index Smart Services - Dumitrescu, Roman; Riemensperger, Frank; Schuh, Günther; Biehler, Jan; Frey, Anna; Hocken, Christian; Koldewey, Christian; Kühn, Arno; Rabe, Martin; Schacht, Maximilian; Comans, Sebastian; Fichtler, Timm; et al.

Accelerating Concept Learning via Sampling - Baci, Alkid; Heindorf, Stefan (CIKM)

Accelerating the analysis of optical quantum systems using the Koopman operator - Peitz, Sebastian; Hunstig, Anna; Rose, Hendrik; Meier, Torsten
The prediction of photon echoes is an important technique for gaining an understanding of optical quantum systems. However, this requires a large number of simulations with varying parameters and/or input pulses, which renders numerical studies expensive. This article investigates how we can use data-driven surrogate models based on the Koopman operator to accelerate this process. In order to be successful, we require a model that is accurate over a large number of time steps. To this end, we employ a bilinear Koopman model using extended dynamic mode decomposition and simulate the optical Bloch equations for an ensemble of inhomogeneously broadened two-level systems. Such systems are well suited to describe the excitation of excitonic resonances in semiconductor nanostructures, for example, ensembles of semiconductor quantum dots. We perform a detailed study on the required number of system simulations such that the resulting data-driven Koopman model is sufficiently accurate for a wide range of parameter settings. We analyze the L2 error and the relative error of the photon echo peak and investigate how the control positions relate to the stabilization. After proper training, the dynamics of the quantum ensemble can be predicted accurately and numerically very efficiently by our methods.

Acceptance of simulation-based assessment formats in teacher education. - Vogelsang, Christoph; Meier, Jana; Janzen, Thomas; Wotschel, Philipp

Achim Duchow: Blindes Vertrauen / Werkverzeichnis 1971–1993
Das Werkverzeichnis des Düsseldorfer Malers, Fotografen und Objektkünstlers Achim Duchow (1948 – 1993) lädt ein zur Wiederentdeckung eines komplexen OEuvres. Im spielerischen Umgang mit Autorschaft, Subjektivität und Medien, dem unmittelbaren Zugriff auf alle ihn bewegenden Themen ist ein Werk entstanden, das auch heute noch seine Wirkung entfaltet. In chronologischer Folge, unterbrochen von einzelnen Essays verzeichnet die Publikation als eine über 400-seitige Liste alle Phasen des Werks: Duchows Zusammenarbeit mit Sigmar Polke in den 1970er Jahren, seinen zweieinhalbjährigen Aufenthalt in Japan, seine Rückkehr 1981 in eine Kunstszene, die sich rasant in Richtung Marktgängigkeit verändert hatte, seine Arbeit an einem neuen Selbstverständnis als Künstler und Kulturarbeiter, seine malerische Auseinandersetzung mit deutscher Geschichte und Politik, mit Kolonialismus und Wiedervereinigung, aber auch mit dem Informel und dem Konstruktivismus. Das Werkverzeichnis katalogisiert alle auffindbaren Arbeiten sowie Texte von Duchow selbst. Weggefährt·innen und Historiker·innen geben einen Einblick in den radikalen Kontext seines Lebens.
Keywords: Malerei; Medienkunst; Fotografie; Düsseldorf; Hamburg; Japan; Bad Painting; Popart; Montage

Acquis communautaire - Krimphove, Dieter (Manz Online)

Action outcome probability influences the size of the head-fake effect in basketball - Güldenpenning, Iris; Jackson, Robin C.; Weigelt, Matthias (Psychology of Sport and Exercise)
Keywords: Applied Psychology

Adaptation to context information for head fakes in basketball - Güldenpenning, Iris; Böer, Nils Tobias; Kunde, Wilfried; Weigelt, Matthias (Abstracts of the 65th Conference of experimental Psychologists (TeaP))

Adaptive Koopman-Based Models for Holistic Controller and Observer Design - Junker, Annika; Pape, Keno Egon Friedrich; Timmermann, Julia; Trächtler, Ansgar (IFAC-PapersOnLine)
Keywords: General Medicine

Adaptive Scaling of Components in the Fused Deposition Modeling Process - Moritzer, Elmar; Hecker, Felix (Macromolecular Symposia)
Abstract Currently, the fused deposition modeling (FDM) process is the most common additive manufacturing technology. The principle of the FDM process is the strand wise deposition of molten thermoplastic polymers, by feeding a filament trough a heated nozzle. Due to the strand and layer wise deposition the cooling of the manufactured component is not uniform. This leads to dimensional deviations which may cause the component to be unusable for the desired application. In this paper, a method is described which is based on the shrinkage compensation through the adaption of every single raster line in components manufactured with the FDM process. The shrinkage compensation is based on a model resulting from a DOE which considers the main influencing factors on the shrinkage behavior of raster lines in the FDM process. An in‐house developed software analyzes the component and locally applies the shrinkage compensation with consideration of the boundary conditions, e.g., the position of the raster line in the component and the process parameters. Following, a validation using a simple geometry is conducted to show the effect of the presented adaptive scaling method.
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; Condensed Matter Physics

Adaptive Scaling of Components in the Fused Deposition Modeling Process - Moritzer, Elmar; Hecker, Felix (Macromolecular Symposia)
Abstract Currently, the fused deposition modeling (FDM) process is the most common additive manufacturing technology. The principle of the FDM process is the strand wise deposition of molten thermoplastic polymers, by feeding a filament trough a heated nozzle. Due to the strand and layer wise deposition the cooling of the manufactured component is not uniform. This leads to dimensional deviations which may cause the component to be unusable for the desired application. In this paper, a method is described which is based on the shrinkage compensation through the adaption of every single raster line in components manufactured with the FDM process. The shrinkage compensation is based on a model resulting from a DOE which considers the main influencing factors on the shrinkage behavior of raster lines in the FDM process. An in‐house developed software analyzes the component and locally applies the shrinkage compensation with consideration of the boundary conditions, e.g., the position of the raster line in the component and the process parameters. Following, a validation using a simple geometry is conducted to show the effect of the presented adaptive scaling method.
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; Condensed Matter Physics

Adding Why to What? Analyses of an Everyday Explanation - Terfloth, Lutz; Schaffer, Michael; Buhl, Heike M.; Schulte, Carsten
In XAI it is important to consider that, in contrast to explanations for professional audiences, one cannot assume common expertise when explaining for laypeople. But such explanations between humans vary greatly, making it difficult to research commonalities across explanations. We used the dual nature theory, a techno-philosophical approach, to cope with these challenges. According to it, one can explain, for example, an XAI's decision by addressing its dual nature: by focusing on the Architecture (e.g., the logic of its algorithms) or the Relevance (e.g., the severity of a decision, the implications of a recommendation). We investigated 20 game explanations using the theory as an analytical framework. We elaborate how we used the theory to quickly structure and compare explanations of technological artifacts. We supplemented results from analyzing the explanation contents with results from a video recall to explore how explainers justified their explanation. We found that explainers were focusing on the physical aspects of the game first (Architecture) and only later on aspects of the Relevance. Reasoning in the video recalls indicated that EX regarded the focus on the Architecture as important for structuring the explanation initially by explaining the basic components before focusing on more complex, intangible aspects. Shifting between addressing the two sides was justified by explanation goals, emerging misunderstandings, and the knowledge needs of the explainee. We discovered several commonalities that inspire future research questions which, if further generalizable, provide first ideas for the construction of synthetic explanations.

Addition und Subtraktion verstehen - Graf, Lara Marie; Wienhues, Inga; Häsel-Weide, Uta (Die Grundschulzeitschrift)

Additive Manufacturing and Mechanical Properties of Auxetic and Non-Auxetic Ti24Nb4Zr8Sn Biomedical Stents: A Combined Experimental and Computational Modelling Approach - Pramanik, Sudipta; Milaege, Dennis; Hein, Maxwell; Hoyer, Kay-Peter; Schaper, Mirko (Crystals)
The effect of plaque deposition (atherosclerosis) on blood flow behaviour is investigated via computational fluid dynamics and structural mechanics simulations. To mitigate the narrowing of coronary artery atherosclerosis (stenosis), the computational modelling of auxetic and non-auxetic stents was performed in this study to minimise or even avoid these deposition agents in the future. Computational modelling was performed in unrestricted (open) conditions and restricted (in an artery) conditions. Finally, stent designs were produced by additive manufacturing, and mechanical testing of the stents was undertaken. Auxetic stent 1 and auxetic stent 2 exhibit very little foreshortening and radial recoil in unrestricted deployment conditions compared to non-auxetic stent 3. However, stent 2 shows structural instability (strut failure) during unrestricted deployment conditions. For the restricted deployment condition, stent 1 shows a higher radial recoil compared to stent 3. In the tensile test simulations, short elongation for stent 1 due to strut failure is demonstrated, whereas no structural instability is noticed for stent 2 and stent 3 until 0.5 (mm/mm) strain. The as-built samples show a significant thickening of the struts of the stents resulting in short elongations during tensile testing compared to the simulations (stent 2 and stent 3). A modelling framework for the stent deployment system that enables the selection of appropriate stent designs before in vivo testing is required. This leads to the acceleration of the development process and a reduction in time, resulting in less material wastage. The modelling framework shall be useful for doctors designing patient-specific stents.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Additively manufactured air-cooled lightweight rotor for an automotive electric motor - Bieber, Maximilian; Haase, Michael; Tasche, Frederik; Zibart, Alexander; Ponick, Bernd (2023 IEEE International Electric Machines & Drives Conference (IEMDC))

Addressing the Unbounded Latency of Best-Effort Device-to-Device Communication with Low Earth Orbit Satellite Support - Franke, Mario; Klingler, Florian; Sommer, Christoph (IEEE Consumer Communications and Networking Conference (CCNC 2023), Track Communication and Applications for Connected and Autonomous Vehicles on Land, Water, and Sky)

Adhesion properties of the hybrid system made of laser-structured aluminium EN AW 6082 and CFRP by co-bonding-pressing process - Wu, Shuang; Delp, Alexander; Freund, Jonathan; Walther, Frank; Haubrich, Jan; Löbbecke, Miriam; Tröster, Thomas (The Journal of Adhesion)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanics of Materials; General Chemistry

Adorno and the Media in Digital Capitalism - Fuchs, Christian (Adorno und die Medien: Kritik, Relevanz, Ethik)

Adsorption of Ferritin at Nanofaceted Al2O3 Surfaces - Pothineni, Bhanu K.; Kollmann, Sabrina; Li, Xinyang; Grundmeier, Guido; Erb, Denise J.; Keller, Adrian (International Journal of Molecular Sciences)
The influence of nanoscale surface topography on protein adsorption is highly important for numerous applications in medicine and technology. Herein, ferritin adsorption at flat and nanofaceted, single-crystalline Al2O3 surfaces is investigated using atomic force microscopy and X-ray photoelectron spectroscopy. The nanofaceted surfaces are generated by the thermal annealing of Al2O3 wafers at temperatures above 1000 °C, which leads to the formation of faceted saw-tooth-like surface topographies with periodicities of about 160 nm and amplitudes of about 15 nm. Ferritin adsorption at these nanofaceted surfaces is notably suppressed compared to the flat surface at a concentration of 10 mg/mL, which is attributed to lower adsorption affinities of the newly formed facets. Consequently, adsorption is restricted mostly to the pattern grooves, where the proteins can maximize their contact area with the surface. However, this effect depends on the protein concentration, with an inverse trend being observed at 30 mg/mL. Furthermore, different ferritin adsorption behavior is observed at topographically similar nanofacet patterns fabricated at different annealing temperatures and attributed to different step and kink densities. These results demonstrate that while protein adsorption at solid surfaces can be notably affected by nanofacet patterns, fine-tuning protein adsorption in this way requires the precise control of facet properties.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Advanced Algorithm Selection with Machine Learning: Handling Large Algorithm Sets, Learning From Censored Data, and Simplyfing Meta Level Decisions - Tornede, Alexander

Advanced Synchronous Rectification for an IGBT-Based ZCS LLC Converter with High Output Currents for a 2 kW Automotive DC-DC Stage - Urbaneck, Daniel; Schafmeister, Frank; Böcker, Joachim (PCIM Europe 2023)
State-of-the-art LLC resonant converters use MOSFETs in their inverter stage, which allows high switching frequencies and thus the use of compact magnetic components. The large parasitic output capacitance and the poor reverse-recovery behaviour of the inherent body diode of high-voltage (600 V) silicon MOSFETs require soft switching, i.e. zero-voltage switching (ZVS). Otherwise, the high turn-on switching losses would lead to excessive heating and ultimately to the destruction of the switch. Therefore, MOSFET-based LLC converters are operated in the so-called inductive region only, which enables ZVS. The use of robust and cost-effective IGBTs instead of MOSFETs is particularly advantageous for automotive applications, since in addition to high reliability low costs are an important objective here. Since IGBTs are characterized by dominant turn-off losses and generally higher switching losses compared to MOSFETs, the aim is to operate them with zero-current switching (ZCS) and at low switching frequencies below the resonance frequency. In this region also the voltage transfer characteristic is steeper, which qualifies for applications with a strongly varying input-to-output voltage ratio, such as given for automotive on-board DC-DC converters connecting the (high-voltage) traction battery with the (12 V) auxiliary battery. In this paper, a stress value analysis based on a switched-model simulation is used to design a ZCS LLC converter and take advantage of the mentioned benefits of IGBTs as well as of the steeper voltage transfer characteristic. Within this operation region below the resonance frequency, however, a new phenomenon of several current pulses occurring during a single switching period through the rectifier components may appear. Generally, in applications with high output currents a synchronous rectifier (SR) is often used to keep the conduction losses of the rectifier stage at a moderate level: Low-voltage MOSFETs, which actively need to be gated synchronously to the polarity of the current pulses, are employed then instead of more lossy rectifier diodes. However, standard SR driver ICs have been shown to be unable to properly rectify the multi-pulse output currents of the proposed LLC operation, resulting in high conduction losses of the rectifier stage. A cost-effective hardware concept is presented which ensures proper rectification by using standard SR-ICs that are actively overdriven by the converter’s central microcontroller. A 2 kW prototype for an EV on-board DC-DC converter was built to show the effectiveness of the method, documenting an increase in efficiency by up to 4.1 % compared to a purely SR-IC-based solution. Overall efficiency is very similar to that of a conventional (MOSFET-based) LLC converter so that the ZCS-operated LLC IGBT-converter represents a cost-effective alternative, which even shows 10 % less worst-case losses.
Keywords: LLC Converter; IGBT; ZCS; Synchronous Rectification

Advanced Synchronous Rectification for an IGBT-Based ZCS LLC Converter with High Output Currents for a 2 kW Automotive DC-DC Stage - Urbaneck, Daniel; Böcker, Joachim; Schafmeister, Frank (PCIM Europe 2023; IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management)

Advances In RTM Manufacturing Of Metal-FRP Hybrids By Self-Sealing And In-Mold Cleaning Techniques - Chalicheemalapalli Jayasankar, Deviprasad
The importance of fiber-reinforced plastics for lightweight construction applications is steadily increasing due to their outstanding weight-specific property values. However, a decisive disadvantage of these composite materials has so far been the high material and process costs, which is why fiber-reinforced plastics are almost exclusively used in small to medium-sized series. Optimization of manufacturing methods is of great importance to reduce the production cost. In this study, two concepts are proposed that can optimize vacuum assisted light resin transfer molding (VA-LRTM) further, leading to a possibility of fully automatic process. Conventional VA-LRTM methods are used to produce complex fiber-reinforced plastics (FRP) and hybrid components. Traditional molds used to produce components via VA-LRTM are sealed using polymer materials to prevent the leakage of matrix system. The seals undergo tremendous amounts of thermal, chemical, and mechanical loadings. Thus, sealings must be replaced in short intervals. In the current study, a concept where sealing is achieved by accelerating the curing of matrix system itself with the help of heating elements and catalysts resulting in a self-sealing approach is proposed. Another concern is mold surface contamination during component production. To address this, a modified automatic cleaning technique based on ultrasonic cleaning was proposed which can be integrated into the production line with minimum modification. Both the proposed concepts were validated and optimized using experiments, simulations, and analytical approaches by producing metal-FRP hybrid shafts.
Keywords: fiber-reinforced plastics; resin transfer molding; composites

AEUV - Krimphove, Dieter (Manz Online)

After-school sports programmes and social inclusion processes in culturally diverse contexts: Results of an international multicase study - Carter-Thuillier, Bastian; López-Pastor, Víctor; Gallardo-Fuentes, Francisco; Carter-Beltran, Juan; Fernández-Balboa, Juan-Miguel; Delgado-Floody, Pedro; Grimminger-Seidensticker, Elke; Sortwell, Andrew (Frontiers in Psychology)
This research aimed to understand the role of after-school sports programs in social inclusion processes in culturally diverse contexts through a multicase study within two locations. The first location was in Spain where immigrant and Spanish students were enrolled, and the other was in Chile with Mapuche-Huilliche students, immigrant and Chilean students. The implemented programs at both sites were similar in their educational focus on socio-educational values, and teaching models (hybridization of teaching games for understanding and cooperative learning) that enhance social inclusion. Using individual and group interviews with teachers, sports coordinators, parents, and students, a qualitative approach was used to identify the factors that facilitate or hinder the social inclusion processes. In addition, the researchers used qualitative observations of the programs over six months using “notes logbook” to record their impressions during the observation process. Results indicated that the implemented sports programs successfully facilitated social inclusion processes, enabling the development of interpersonal skills and relationships between students from different cultural backgrounds. The previous training and experiences of teachers in culturally diverse contexts, and incorporation of traditional sporting games from all cultures, seems to be an important facilitator factor for the inclusion potential of the implemented programs.
Keywords: General Psychology

Agentenbasierte Modellierung und Simulation im Pandemiemanagement - Hälterlein, Jens (TATuP - Zeitschrift für Technikfolgenabschätzung in Theorie und Praxis)
Mathematical models and computer simulations play a crucial role in the context of the COVID-19 crisis for knowledge about the possible course of the pandemic and for appropriate policy decisions. The paper presents results from an ethnographic study of a government-funded R & D project dealing with agent-based modeling and simulation (ABMS) in the context of pandemic management. Based on the assumption that the use of computer simulations in pandemic management is not only a means to an end for political or epidemiological goals but also plays a significant role in determining which goals and strategies appear politically legitimate, the paper reconstructs how insights into the pandemic are generated in ABMS and specifically in the researched project and made accessible for decision-making.
Keywords: General Medicine

Aggregating Human Domain Knowledge for Feature Ranking - Kornowicz, Jaroslaw; Thommes, Kirsten (Artificial Intelligence in HCI)

Agile Tools für agile Didaktik - Osthushenrich, Judith; Neiske, Iris (Inverted Classroom and beyond 2023: Agile Didaktik für nachhaltige Bildung)
Dieser Tagungsband greift vielfältige Impulse der Konferenz, die unter dem Motto „Agile Didaktik für nachhaltige Entwicklung“ stand, auf. Damit wird eine spannende und inspirierende weitere Auseinandersetzung mit den angesprochenen Themenschwerpunkten unterstützt. Gleichzeitig wird einmal mehr deutlich, dass das Inverted-Classroom-Modell nicht auf eine spezielle Fachdisziplin oder ausgewählte Lehrveranstaltungsformate beschränkt ist. Es ist ein Mindset und gleichzeitig eine Einladung für die Weiterentwicklung agiler Bildung für nachhaltige Entwicklung. Geliefert werden weiters viele Impulse, die Anregungen für die Hochschuldidaktik sowie für die strategische Ausrichtung von Hochschulen bringen, die dann noch stärker Mitverantwortung für gesellschaftliche Transformationsprozesse übernehmen, mehr noch, diese in vieler Hinsicht aktiv mitgestalten.

AI Washing: The Framing Effect of Labels on Algorithmic Advice Utilization - Leffrang, Dirk (International Conference on Information Systems)
Many researchers and practitioners see artificial intelligence as a game changer compared to classical statistical models. However, some software providers engage in “AI washing”, relabeling solutions that use simple statistical models as AI systems. By contrast, research on algorithm aversion unsystematically varied the labels for advisors and treated labels such as "artificial intelligence" and "statistical model" synonymously. This study investigates the effect of individual labels on users' actual advice utilization behavior. Through two incentivized online within-subjects experiments on regression tasks, we find that labeling human advisors with labels that suggest higher expertise leads to an increase in advice-taking, even though the content of the advice remains the same. In contrast, our results do not suggest such an expert effect for advice-taking from algorithms, despite differences in self-reported perception. These findings challenge the effectiveness of framing intelligent systems as AI-based systems and have important implications for both research and practice.
Keywords: Artificial Intelligence; Algorithm Appreciation; Framing; Advice-taking; Expertise

Aktuelle Lehrer:innenbildung für Inklusion. Ausgangspunkte, Herausforderungen und Gestaltungsmöglichkeiten für studienganggemischte Seminargruppen. Impulsvortrag am Zentrum für Lehrkräftebildung, Universität Duisburg-Essen - Büker, Petra
Juni 2023

Al Vostro Servizio - Schulze, Max (Buch Handlung Welt Bücher)
Buch Handlung Welt – in drei Worten − wurde von der Künstlerin Hilka Nordhausen 1976 im Hamburger Karolinenviertel eröffnet. Ein Laden, der Unmengen an Drucken, Heften, Broschüren, Taschenbüchern, Publikationen aus dem Underground, aus Übersee, der Kunst und Esoterik, auch selbstverlegte Bücher, Kataloge und Zines versammelte, die in wirren Stapeln halbhohe Tische bedeckten. Zwischen den überquellenden Bücherregalen fanden Lesungen und Performances statt, Filme und alles mögliche andere wurden projiziert. Fast jeden Monat entstand ein neues Wandbild in den Räumen. Die Buch Handlung Welt war bis 1983 in Hamburg der Ort für selbstorganisiertes künstlerisches Handeln − ein Anschlag auf die Wirklichkeit. Ein Konvolut dieser Bücher und Zeitschriften befindet sich im Nachlass von Hilka Nordhausen. 40 Jahre später stellt sich die Frage: Was bleibt von den Büchern, welchen Zeitgeist transportieren sie? Welche haben auch heute noch Bedeutung? Dieses Buch versammelt eine Reihe von subjektiven und widersprüchlichen Einschätzungen zu diesen Titeln, von jungen und mittelalten Künstler*innen und Wissenschaftler*innen.
Keywords: Buch Handlung Welt; Hilka Nordhausen; Achim Duchow; Martin Kippnberger

Algebra: Leitidee Symbol und Formalisierung - Hefendehl-Hebeker, Lisa; Rezat, Sebastian (Handbuch der Mathematikdidaktik)

Algorithmic Fairness in AI - Pfeiffer, Jella; Gutschow, Julia; Haas, Christian; Möslein, Florian; Maspfuhl, Oliver; Borgers, Frederik; Alpsancar, Suzana (Business & Information Systems Engineering)
Keywords: Information Systems

Algorithms for the genome median under a restricted measure of rearrangement - Silva, Helmuth O.M.; Rubert, Diego P.; Araujo, Eloi; Steffen, Eckhard; Doerr, Daniel; Martinez, Fábio V. (RAIRO - Operations Research)
Ancestral reconstruction is a classic task in comparative genomics. Here, we study the genome median problem, a related computational problem which, given a set of three or more genomes, asks to find a new genome that minimizes the sum of pairwise distances between it and the given genomes. The distance stands for the amount of evolution observed at the genome level, for which we determine the minimum number of rearrangement operations necessary to transform one genome into the other. For almost all rearrangement operations the median problem is NP-hard, with the exception of the breakpoint median that can be constructed efficiently for multichromosomal circular and mixed genomes. In this work, we study the median problem under a restricted rearrangement measure called c4-distance, which is closely related to the breakpoint and the DCJ distance. We identify tight bounds and decomposers of the c4-median and develop algorithms for its construction, one exact ILP-based and three combinatorial heuristics. Subsequently, we perform experiments on simulated data sets. Our results suggest that the c4-distance is useful for the study the genome median problem, from theoretical and practical perspectives.
Keywords: Management Science and Operations Research; Computer Science Applications; Theoretical Computer Science

Alignment between timing of ‘highest caloric intake’ and chronotype in relation to body composition during adolescence: the DONALD Study - Jankovic, Nicole; Schmitting, Sarah; Stutz, Bianca; Krüger, Bettina; Buyken, Anette; Alexy, Ute (European Journal of Nutrition)
Abstract Purpose Our aim was to assess alignment in timing of ‘highest caloric intake’ with individual chronotype and its association with body composition in adolescents. Methods We used repeatedly collected data from n = 196 adolescents (age 9–16 years, providing N = 401 yearly questionnaires) of the DONALD open cohort study. Chronotype was assessed by the Munich Chronotype Questionnaire from which midpoint of sleep (MSFsc) was derived. A sex- and age-specific diet-chrono-alignment score (DCAS) was calculated as the difference in hours between the chronotype-specific median timing of highest caloric intake of the studied population and the individual timing of ‘highest caloric intake’ or vice versa. Repeated-measures regression models were applied to study cross-sectional and longitudinal associations between the DCAS and body composition, e.g., Fat Mass Index (FMI) or Fat Free Mass Index (FFMI). Results DCAS ranged from −6:42 h to + 8:01 h and was not associated with body composition. Among adolescents with a later chronotype ( N = 201) a 1 h increase in DCAS (later consumption of ‘highest caloric intake’ in comparison to the median intake of that group), increased FFMI by 1.92 kg/m 2 (95% CI: 0.15, 3.69, p value = 0.04) over a median follow-up of 0.94 year. Conclusion Alignment of energy intake with individual chronotype appears beneficial for FFMI among those with a late chronotype.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

All optical operation of a superconducting photonic interface - Thiele, Frederik; Hummel, Thomas; McCaughan, Adam N.; Brockmeier, Julian; Protte, Maximilian; Quiring, Victor; Lengeling, Sebastian; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Optics Express)
Quantum photonic processing via electro-optic components typically requires electronic links across different operation environments, especially when interfacing cryogenic components such as superconducting single photon detectors with room-temperature control and readout electronics. However, readout and driving electronics can introduce detrimental parasitic effects. Here we show an all-optical control and readout of a superconducting nanowire single photon detector (SNSPD), completely electrically decoupled from room temperature electronics. We provide the operation power for the superconducting detector via a cryogenic photodiode, and readout single photon detection signals via a cryogenic electro-optic modulator in the same cryostat. This method opens the possibility for control and readout of superconducting circuits, and feedforward for photonic quantum computing.
Keywords: Atomic and Molecular Physics; and Optics

Alles anders und doch gleich?! - Auswirkungen der Digitalisierung und Folgen der Covid-19-Pandemie auf die unterrichtsbezogene Lehrerkooperation - Engemann, Mario; Herzig, Bardo

Allowing the Economy to Breathe Even During the Crisis – Interview with Tax Expert Caren Sureth-Sloane - Unterstell, Rembert

Als Lehrkraft gut beraten? Entwicklung und Erprobung eines handlungsnahen Prüfungsformates zur Erfassung von Beratungskompetenz von Lehramtsstudierenden - Wotschel, Philipp; Vogelsang, Christoph; Janzen, Thomas; Meier, Jana

Alterations of postural control across the menstrual cycle – A systematic review - Pohle, Carina; Becker, Linda; Baumeister, Jochen (Gait & Posture)
Keywords: Rehabilitation; Orthopedics and Sports Medicine; Biophysics

Alternative für alle? Inklusionsspezifische Analyse der AfD und ihrer Wähler*innen - Freymuth, Nina (Diskriminierungsprozesse und Teilhabeperspektiven - Herausforderungen für die Praxis der Inklusion. Ausgewählte Master-Thesen 2018-2022 des Masterstudiengangs "Soziale Inklusion: Gesundheit und Bildung" der Evangelischen Hochschule Rheinland-Westfalen-Lippe)

Alterungsmechanismen von Haushaltskältegeräten - Paul, Andreas; Baumhögger, Elmar; Elsner, Andreas; Reineke, Michael; Kasper, Tina; Schumacher, Daniel; Vrabec, Jadran; Hüppe, Christian; Stamminger, Rainer; Hölscher, Heike; Stoll, Ragnar; Wagner, Hendrik; et al.
Die für die Berechnung des Energieeffizienzindex von Haushaltskältegeräten benötigten Parameter werden durch Norm-Messungen im Neuzustand der Geräte bestimmt. Aus früheren Untersuchungen ist bekannt, dass durch verschiedene technische Alterungsmechanismen der Energieverbrauch über eine Produktlebensdauer von 18 Jahren um bis zu 33 % zunehmen kann. Ziel des vom BMWi geförderten Projekts ALGE war es, die verschie-denen Ursachen und Einflussgrößen für die Alterung von Haushaltskältegeräten zu ermitteln und eine Alterungs-funktion zu bestimmen, die den zeitlichen Verlauf des zunehmenden Energieverbrauchs beschreibt. In diesem Projekt wurde das Alterungsverhalten von Haushaltskältegeräten durch 100 Normenergieverbrauchs-messungen an 32 real gealterten Geräten untersucht. Aus den gewonnenen Ergebnissen konnte eine Alterungs-funktion bestimmt werden, die den Anstieg des Energieverbrauchs beschreibt. Alle untersuchten Geräte wurden an der Universität Paderborn im Neuzustand vermessen und nach einer Laufzeit von bis zu 21 Jahren erneut geprüft. Bereits nach einem zweijährigen Betrieb konnte ein Mehrverbrauch von bis zu 11 % festgestellt werden. Über die durchschnittliche Produktlebensdauer von Haushaltskältegeräten von ca. 16 Jahren steigert sich der Energieverbrauch um durchschnittlich 27 %. Im Rahmen des Projekts wurden verschiedene Systemkomponenten, wie Isolierung und Verdichter, hinsichtlich ihres Alterungsverhaltens untersucht. Bei dem im Gehäuse als Isolierung verwendeten PUR-Schaum konnte über einen Zeitraum von 31 Monaten ein Anstieg der Wärmeleitfähigkeit von 19,5 W/(m⋅K) auf 24,5 W/(m⋅K) festge-stellt werden. Zur Untersuchung der Alterung der Verdichter wurden zuvor auf einem Kalorimeterteststand ver-messene Verdichter in Geräte eingebaut. Nach einem zweijährigen Betrieb wurden diese Verdichter wieder aus-gebaut und erneut vermessen. Hierbei konnte keine Änderung des COP festgestellt werden. Zusätzlich zu den technischen Parametern wurde der Einfluss des Verbraucherverhaltens analysiert. Hier zeigte sich, dass bis zu 33 % des Gesamtenergieverbrauchs nach einer mehrjährigen Nutzungsdauer verbraucherinduziert sein können.
Keywords: Haushaltskältegeräte; Energieverbrauch; Alterung; Verdichter; PUR-Schaum

Altis-SYCL: Migrating Altis Benchmarking Suite from CUDA to SYCL for GPUs and FPGAs - Weckert, Christoph; Solis-Vasquez, Leonardo; Oppermann, Julian; Koch, Andreas; Sinnen, Oliver (Proceedings of the SC '23 Workshops of The International Conference on High Performance Computing, Network, Storage, and Analysis)

Ambivalenzkompetenz? Rückblick auf die Tagung "Katastrophen". Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert am Vortag des russischen Angriffs auf die Ukraine - Schroeter-Wittke, Harald; Breckner, Anne (Katastrophen. Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert)

Ambivalenzkompetenz? Rückblick auf die Tagung 'Katastrophen'. Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert am Vortag des russischen Angriffs auf die Ukraine - Breckner, Anne; Schroeter-Wittke, Harald (Katastrophen. Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert)

Ambroise Paré and René Descartes on Sensation in Amputated Limbs - Muller, Jil (Descartes and Medicine Problems, Responses and Survival of a Cartesian Discipline)

An approach for the numerical calculation of the non-isothermal pressure-throughput-characteristics of single screw melt-extruder - Stüker, Daniel; Schöppner, Volker (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

An eigenen Fällen lernen. Überlegungen zur lern- und entwicklungsorientierten Fallarbeit in der Religionslehrer:innenbildung - Caruso, Carina; Woppowa , Jan (Religionslehrer:in im 21. Jahrhundert. Transformationsprozesse im Beruf und theologisch-religionspädagogischer Bildung in Studium, Referendariat und Fortbildung)

An Evaluation of XCS on the OpenAI Gym - Mehlich, Florian

An Experimental and Computational Modeling Study on Additively Manufactured Micro‐Architectured Ti–24Nb–4Zr–8Sn Hollow‐Strut Lattice Structures - Pramanik, Sudipta; Milaege, Dennis; Hein, Maxwell; Andreiev, Anatolii; Schaper, Mirko; Hoyer, Kay-Peter (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science

An IAD framework analysis of minigrid institutions for sustainable rural electrification in East Africa: A comparative study of Uganda and Tanzania - Namujju, Lillian Donna; Acquah-Swanzy, Henrietta; Ngoti, Irene F. (Energy Policy)
Keywords: Management; Monitoring; Policy and Law; General Energy

An integrated decision support framework for resilient vaccine supply chain network design - Tirkolaee, Erfan Babaee; Torkayesh, Ali Ebadi; Tavana, Madjid; Goli, Alireza; Simic, Vladimir; Ding, Weiping (Engineering Applications of Artificial Intelligence)
Keywords: Electrical and Electronic Engineering; Artificial Intelligence; Control and Systems Engineering

An integrated group fuzzy inference and best–worst method for supplier selection in intelligent circular supply chains - Tavana, Madjid; Sorooshian, Shahryar; Mina, Hassan (Annals of Operations Research)

An Integrative View of the Transformations towards Sustainability and Digitalization: The Case for a Dual Transformation - Kürpick, Christian; Rasor, Anja; Scholtysik, Michel; Kühn, Arno; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

An interval multi-criteria decision-making model for evaluating blockchain-IoT technology in supply chain networks - Tavana, Madjid; Khalili Nasr, Arash; Ahmadabadi, Alireza Barati; Amiri, Alireza Shamekhi; Mina, Hassan (Internet of Things)
Keywords: Management of Technology and Innovation; Artificial Intelligence; Computer Science Applications; Hardware and Architecture; Engineering (miscellaneous); Information Systems; Computer Science (miscellaneous); Software

An optimization model with a lagrangian relaxation algorithm for artificial internet of things-enabled sustainable circular supply chain networks - Tavana, Madjid; Khalili Nasr, Arash; Santos-Arteaga, Francisco J.; Saberi, Esmaeel; Mina, Hassan (Annals of Operations Research)

An Optimized Third-Harmonic Injection Reduces DC-Link Voltage Ripple in Cascaded H-Bridge Converters up to 50% for all Power Factors - Unruh, Roland; Böcker, Joachim; Schafmeister, Frank (2023 25th European Conference on Power Electronics and Applications (EPE'23 ECCE Europe))
Star-connected cascaded H-bridge Converters require large DC-link capacitors to buffer the second-order harmonic voltage ripple. First, it is analytically proven that the DC-link voltage ripple is proportional to the apparent converter power and does not depend on the power factor for nominal operation with sinusoidal reference arm voltages and currents. A third-harmonic zero-sequence voltage injection with an optimal amplitude and phase angle transforms the 2nd harmonic to a 4th harmonic DC-link voltage ripple. This reduces the voltage ripple by exactly 50% for all power factors at steady-state at balanced conditions. However, this requires 54% additional modules for unity power factor operation and even 100% for pure reactive power operation to account for the increased reference arm voltages due to the large amplitude of the optimal third-harmonic injection. If not enough modules are available, an adaptive discontinuous PWM is utilized to still minimize the voltage ripple for the given number of modules and power factor. With a very limited number of modules (modulation index is 1.15), the proposed method still reduces the DC-link voltage ripple by 24.4% for unity power factor operation. It requires the same number of modules as the commonly utilized 3rd harmonic injection with 1/6 of the grid voltage amplitude and achieves superior results. Simulations of a 10 kV/1 MVA system confirm the analysis.
Keywords: Cascaded H-Bridge; Solid-State Transformer; Capacitor voltage ripple; Zero sequence voltage; Third harmonic injection

Analyse von Alterungsmechanismen im Hinblick auf die Effizienz von Haushaltskältegeräten - Paul, Andreas
Die Energieaufnahme von Haushaltskältegeräten ist seit den 1990er Jahren erheblich gesunken. Dieser Wert wird von den Herstellern im Neuzustand der Geräte unter Normbedingungen bestimmt. Wie jedes technische System unterliegen jedoch auch Haushaltskältegeräte einem Alterungsprozess, der zu einem Anstieg der Energieaufnahme über die Zeit führt. Im Rahmen dieser Dissertation wurde auf der Grundlage von 100 Messungen der Energieaufnahme, die an 32 Geräten über einen Zeitraum von 21 Jahren durchgeführt wurden, ein Alterungsmodell entwickelt. Dieses Modell ist das erste, das mit Hilfe von Daten der Energieaufnahme real gealterter Geräte entwickelt wurde. Es beschreibt einen Anstieg der Energieaufnahme von 27 % über die durchschnittliche Einsatzzeit eines Haushaltskältegeräts von 16 Jahren. Der stärkste Anstieg erfolgt in den ersten fünf Betriebsjahren. Durch Diffusionsvorgänge in dem im Gehäuse verbauten Polyurethan-Schaum wird das im Zellgas vorhandene Kohlenstoffdioxid durch Luft ersetzt. Hierdurch steigt die Wärmeleitfähigkeit des Schaums um ca. 33 % an, wodurch sich die Energieaufnahme der Geräte erhöht. Des Weiteren wurde der Einsatz von Paraffinen als Phasenwechselmaterial in Haushaltskältegeräten untersucht. Durch deren Einsatz konnte die Energieaufnahme gesenkt und die Funktionalität der Geräte gesteigert werden. Hierfür sind detaillierte Kenntnisse der Materialkenndaten der Paraffine notwendig. Die Wärmeleitfähigkeit der verschiedenen Paraffin-Stoffgruppen in der festen Phase ist jedoch bisher nur unzureichend untersucht worden. Daher wurde ein Messaufbau entwickelt, mit dem die Wärmeleitfähigkeit von festem Paraffin bestimmt werden kann, und es wurden entsprechende Messungen durchgeführt.

Analysis and Modelling of the Deformation in the Manufacture of Flange-Contours by the Combined Friction-Spinning and Flow-Forming Process - Dahms, Frederik; Homberg, Werner (Lecture Notes in Mechanical Engineering)

Analysis and modelling of the material degradation of polypropylene on the co-rotating twin-screw extruder - Altepeter, Matthias; Wanke, Sven; Schöppner, Volker (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

Analysis and Optimization of Joint Formation in Hybrid Compression Molding - Lückenkötter, Julian; Aydin, Simon; Marten, Thorsten; Tröster, Thomas

Analysis and Simulation of a Coherent FMCW Lidar-Photonic Radar Combined Sensor System for Large Aperture Phased Array MIMO - Kruse, Stephan; Meinecke, Marc-Michael; Kneuper, Pascal; Schwabe, Tobias; Kurz, Heiko G.; Scheytt, J. Christoph (2023 20th European Radar Conference (EuRAD))

Analysis of a chemotaxis-SIS epidemic model with unbounded infection force - Tao, Youshan; Winkler, Michael (Nonlinear Analysis: Real World Applications)
Keywords: Applied Mathematics; Computational Mathematics; General Economics; Econometrics and Finance; General Engineering; General Medicine; Analysis

Analysis of Phase Noise in Waveguide-integrated Optical Test Structures in Silicon Photonics - Surendranath Shroff, Vijayalakshmi; Kress, Christian; Bahmanian, Meysam; Scheytt, J. Christoph (2023 PhotonIcs & Electromagnetics Research Symposium (PIERS),)
This paper experimentally investigates and interprets the e®ects of noise and non- linearity in a silicon photonic optical test structure. For the analysis di®erent optoelectronic phase noise measurement techniques are used. Our tests focuses on the performance of integrated opti- cal test structures using femtosecond pulses in the 1550nm spectral range. A primary objective is to understand the behaviour of silicon photonic waveguides that can be further employed in the implementation of an optoelectronic phase-locked loop (OEPLL) in silicon photonics technology. A comparison of our results, as well as a discussion on the di®erent optoelectronic phase noise measurement techniques are presented. Our ¯ndings provide insights that can be leveraged to optimize the design and performance of ultra-low phase noise on-chip OEPLL systems locking to mode-locked laser (MLL) signals. In the future such systems can be essential for advanced communication and sensing applications.

Analysis of temperature effect on strength and microstructure in friction induced recycling process (FIRP) - Borgert, Thomas; Homberg, Werner (Materials Research Proceedings)
Abstract. In order to reduce global energy consumption in production and industry along with the associated CO2 emissions, existing resources must be used more efficiently. This includes the energy-efficient and comprehensive recycling of a wide range of metals. Especially for the production of aluminium, there is a large potential for saving energy using efficient recycling processes. With regard to the recycling of aluminium studies have shown that solid-state recycling processes are significantly more efficient considering the used energy and resources compared to the conventional, smelting-metallurgical recycling process. In this paper, the direct and energy-efficient friction-induced recycling process (FIRP) based on the conform process is further described and analysed in terms of the temperature-property relationships. For this purpose, the influence of the processing temperature on the microstructure and properties of the recycled semi-finished products is investigated using the toll system that enables an ECAP forming. Specific sections of the (in theory) infinite, recycled semi-finished product are taken and analysed at different process temperatures of the solid state recycling process. Based on these sections, the properties in terms of mechanical hardness, strength, ductility and grain size are analysed and a degressive relationship between process temperature and mechanical hardness up to a temperature of 270 °C can be shown. Applying the Hall-Petch relationship, it is analysed whether there is a correlation between the strength and the microstructure in the form of the grain size.
Keywords: Recycling; Aluminium; Friction-Induced; Energy Efficiency

Analysis of the nonlinear optical response of excitons in type-I and type-II quantum wells including many-body correlations - Meier, Torsten; Trautmann, Alexander; Stein, M.; Schäfer, F.; Anders, D.; Ngo, C.; Steiner, J. T.; Reichelt, Matthias; Chatterjee, S. (Ultrafast Phenomena and Nanophotonics XXVII)
The nonlinear optical response of quantum well excitons excited by optical fields is analyzed by numerical solutions of the semiconductor Bloch equations. Differential absorption spectra are computed for resonant pumping at the exciton resonance and the dependence of the absorption changes on the polarization directions of the pump and probe pulses is investigated. Coherent biexcitonic many-body correlations are included in our approach up to third-order in the optical fields. Results are presented for spatially-direct type-I and spatiallyindirect type-II quantum well systems. Due to the spatial inhomogeneity, in type-II structures a finite coupling between excitons of opposite spins exists already on the Hartree-Fock level and contributes to the absorption changes for the case of opposite circularly polarized pump and probe pulses.

Analytic hierarchy process and data envelopment analysis: A match made in heaven - Tavana, Madjid; Soltanifar, Mehdi; Santos-Arteaga, Francisco J.; Sharafi, Hamid (Expert Systems with Applications)
Keywords: Artificial Intelligence; Computer Science Applications; General Engineering

Analytical hierarchy process: revolution and evolution - Tavana, Madjid; Soltanifar, Mehdi; Santos-Arteaga, Francisco J. (Annals of Operations Research)
Keywords: Management Science and Operations Research; General Decision Sciences

Analyzing the Generalizability of Automated Algorithm Selection: A Case Study for Numerical Optimization - Ŝkvorc, Urban; Eftimov, Tome; Koro]ec, Peter (2023 IEEE Symposium Series on Computational Intelligence (SSCI))

Analyzing the Interface Between Mathematics and Engineering in Basic Engineering Courses - Kortemeyer, Jörg; Biehler, Rolf (Practice-Oriented Research in Tertiary Mathematics Education)

Analyzing the Needs of Ukrainian Refugees on Telegram in Real-Time: A Machine Learning Approach - Reimann, Raphael; Caron, Matthew (Wirtschaftsinformatik)
The humanitarian crisis resulting from the Russian invasion of Ukraine has led to millions of displaced individuals across Europe. Addressing the evolving needs of these refugees is crucial for hosting countries and humanitarian organizations. This study leverages social media analytics to supplement traditional surveys, providing real-time insights into refugee needs by analyzing over two million messages from Telegram, a vital platform for Ukrainian refugees in Germany. We employ Natural Language Processing techniques, including language identification, sentiment analysis, and topic modeling, to identify well-defined topic clusters such as housing, financial and legal assistance, language courses, job market access, and medical needs. Our findings also reveal changes in topic occurrence and nature over time. To support practitioners, we introduce an interactive web-based dashboard for continuous analysis of refugee needs.

Anchoring and electro-optic switching of liquid crystals on nano-structured surfaces fabricated by two-photon based nano-printing - Zhang, Bingru; Plidschun, Malte; Schmidt, Markus A.; Kitzerow, Heinz-Siegfried (Optical Materials Express)
The alignment of liquid crystals on surfaces plays a central role in optimizing their performances. In this work, a cutting-edge nano-lithography-based method to control the local orientation of a thermotropic liquid crystal is applied to easily available commercial standard materials and evaluated. Parallel nanogrooves on a substrate, created through 3D nanoprinting in a negative-tone photoresin optimized for two-photon polymerization are used for this purpose. Azimuthal anchoring energies of the order from 10 −6 J/m 2 to 10 −5 J/m 2 are found, depending on the spacing, width and depth of the grooves. In part, these values are larger than those reported previously for another photopolymer. Both uniform alignment and spatial patterns of different alignment directions can be realized. Electro-optic studies confirm the suitability of the method for electrically addressable photonic applications and indicate strong polar anchoring.
Keywords: Electronic; Optical and Magnetic Materials

Angelica Dinger: Basileia bei Origenes. Historisch-semantische Analysen im Matthäuskommentar. Beiträge zur historischen Theologie 194. Mohr Siebeck, Tübingen 2020, 338 S. - Schroeter-Wittke, Harald (Paderborner Historische Mitteilungen)

Angst, Glaube und Liebe in M. Night Shyamalans „The Village“ - Pinsch, Jan Christian (tà katoptrizómena – Magazin für Kunst | Kultur | Theologie | Ästhetik)

Anmerkungen zum Begriff des digitalen Kapitalismus. - Christian, Fuchs (Theorien des digitalen Kapitalismus)

AnnoPy – Ein digitales Tool zur Förderung von Textkompetenzen. - Rezat, Sara; Scholle, Oliver (Medien im Deutschunterricht)

AnnoPy. Ein digitales Tool zur Förderung von Textkompetenzen - Rezat, Sara; Scholle, Oliver (Medien im Deutschunterricht)
Im Beitrag wird ein digitales Tool zur fächerübergreifenden Förderung von Textkompetenzen vorgestellt. Zunächst werden die Funktionen des Tools beschrieben und das zugrundeliegende tool-based task Design erläutert. Anhand eines Lehr-Lern-Arrangements zum argumentierenden Schreiben wird exemplarisch gezeigt, wie das Tool im Deutschunterricht eingesetzt werden kann. Anschließend werden erste empirische Befunde aus der am Design-Based-Research orientierten Studie vorgestellt. Abstract (english): AnnoPy – A digital tool for cross-curricular text literacy development In this article we present a digital tool for cross-curricular text literacy development. At first, we describe the basic functions of the tool and the underlying tool-based task design. After that, a teaching arrangement for German lessons is used to show how the tool can be used to foster argumentative writing. Subsequently, first results of the design-based study are presented.
Keywords: Textkompetenz; Digitales Lesen und Schreiben; Kollaborativer Umgang mit Texten; Prozedurenorientierte Schreibdidaktik; Design-based-Research

Annotation uncertainty in the context of grammatical change - Merten, Marie-Luis; Wever, Marcel; Tophinke, Doris; Geierhos, Michaela; Hüllermeier, Eyke (International Journal of Corpus Linguistics)

Anrisserkennung an geclinchten Proben während einer zyklischen Belastung unter Nutzung eines Scanning Laser Doppler Vibrometers - Brosius, Alexander; Ewenz, Lars; Stephan, Richard; Zimmermann, Martina (Tagung Werkstoffprüfung 2022)

Anthropologie - strittig zwischen Christentum und Islam? - Tatari, Muna; Ströbele, Christian (Herausforderung Mensch)

Anticipatory Assignment of Passengers to Meeting Points for Taxi-Ridesharing - Dieter, Peter; Stumpe, Miriam; Ulmer, Marlin Wolf; Schryen, Guido (Transportation Research Part D)

Antimicrobial Brushes on Titanium via “Grafting to” Using Phosphonic Acid/Pyridinium Containing Block Copolymers - Methling, Rafael; Dückmann, Oliver; Simon, Frank; Wolf‐Brandstetter, Cornelia; Kuckling, Dirk (Macromolecular Materials and Engineering)
Abstract Coating medical implants with antibacterial polymers may prevent postoperative infections which are a common issue for conventional titanium implants and can even lead to implant failure. Easily applicable diblock copolymers are presented that form polymer brushes via “grafting to” mechanism on titanium and equip the modified material with antibacterial properties. The polymers carry quaternized pyridinium units to combat bacteria and phosphonic acid groups which allow the linear chains to be anchored to metal surfaces in a convenient coating process. The polymers are synthesized via reversible‐addition‐fragmentation‐chain‐transfer (RAFT) polymerization and postmodifications and are characterized using NMR spectroscopy and SEC. Low grafting densities are a major drawback of the “grafting to” approach compared to “grafting from”. Thus, the number of phosphonic acid groups in the anchor block are varied to investigate and optimize the surface binding. Modified titanium surfaces are examined regarding their composition, wetting behavior, streaming potential, and coating stability. Evaluation of the antimicrobial properties revealed reduced bacterial adhesion and biofilm formation for certain polymers, albeit the cell biocompatibility against human gingival fibroblasts is also impaired. The presented findings show the potential of easy‐to‐apply polymer coatings and aid in designing next‐generation implant surface modifications.
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; General Chemical Engineering

Antonia Villinger: Dramen der Schwangerschaft. Friedrich Hebbels „Judith“, „Maria Magdalena“ und „Genoveva“. Baden-Baden: Ergon 2021 - Famula, Marta (Jahrbuch Forum Vormärz Forschung 2022. [in Vorbereitung])

Anvil-free ultrasonic welding for welding situations with one sided access - Schöppner, Volker; Arndt, Theresa (76th Annual Assembly of the International Institute of Welding (IIW))

Apocalypse Now (Again)!, Spielarten der Apokalypse in ethischen Kontexten.

Apocalypse Now? Endzeitphantasmen bei Wilhelm Genazino und Markus Orths - Süwolto, Leonie (Werke im Dialog. (Virtuelle) Begegnungen in 40 Jahren ‚Paderborner Gastdozentur für Schriftstellerinnen und Schriftsteller‘)

Apologie für das Nebensächliche. Prinzipien einer intersektional orientierten Unterrichtsmodel-lierung am Beispiel von Aneignungsperspektiven zu einer jugendpopulären Fernsehserie - Kißling, Magdalena (Rassismussensibler Literaturunterricht – Grundlagen, Dimensionen, Herausforderungen, Möglichkeiten)

Application of a new strategy for time-efficient laser treatment of galvanized steel substrates to improve the adhesion properties - Voswinkel, Dietrich (Journal of Manufacturing Processes)
Laser structuring to improve the adhesion properties of steel substrates in fiber-metal laminates offers many advantages that are highly suitable for modern industrial requirements. Maintenance and energy costs are relatively low, it is easy to automate, and there are no by-products such as chemicals or abrasives to dispose of or recycle. This makes laser structuring a particularly environmentally friendly process, which is nowadays more important than ever. On the other hand, the process time for laser structuring is much higher than for chemical pre-treatment, for example. In past studies, the time and cost efficiency of the laser structuring process has tended to play a minor role. However, there are approaches in which laser structured surfaces are adapted to the shear stress peaks occurring within the adhesive layer, thus requiring only partial structuring of the area to be bonded, potentially saving process time. In this experimental study, electrolytically galvanized steel substrates were partially laser structured to match the shear stress distribution and then bonded to a carbon fiber-reinforced plastic. The adhesion properties achieved were characterized using shear tensile tests and compared with the properties of the fully structured ones. With the partial laser structuring, a saving of 66 % of the conventional process time was achieved while maintaining 95 % of the same shear strength.
Keywords: Laser treatment Adhesive bonding Surface technology Hybrid materials

Application-based learning of signal analysis methods with the help of a graphical open-source software - Hetkämper, Tim; Koch, Kevin; Webersen, Manuel; Claes, Leander (SEFI 51th Annual Conference Proceedings - Engineering Education for Sustainability)